UMP library system (VB system) - Siti Munirah, Kadir (2015)
UMP Library System (VB system) is a system build to enhance the existing system. VB system is the VenueBooking system for UMP Library. This system will help user to book the facilities provide by UMP Library. The purpose of this project is to help user to make reservation, to help user make missing book report and will help user to know the upcoming activities. In order to build the prototype, waterfall model is used as the methodology.